Comparative Efficacy of Chinese Herbal Injections for the Treatment of Herpangina: A Bayesian Network Meta-Analysis of Randomized Controlled Trials - Duan, Xiaojiao; Wang, Haojia; Wu, Jiarui; Zhou, Wei; Wang, Kaihuan; Liu, Xinkui (Frontiers in Pharmacology, 2020)
Background: Considering the limitations of broad-spectrum antiviral drugs for the treatment of herpangina and the extensive exploration of Chinese herbal injections (CHIs), systematic evaluation of the efficacy of different CHIs in the treatment of herpangina is a key imperative. In this study, we performed a network meta-analysis to investigate the efficacy of CHIs, including Reduning injection (RDN), Shuanghuanglian injection (SHL), Tanreqing injection (TRQ), Xiyanping injection (XYP), and Yanhuning injection (YHN), in the treatment of herpangina. Methods: A systematic literature review was conducted in several databases. The quality of the included studies was assessed using the Cochrane risk of bias tool. Data were analyzed using the STATA 13.0 and WinBUGS 1.4.3 software. Surface under the cumulative ranking curve (SUCRA) probability values were applied to rank the examined treatments. Clustering analysis was performed to compare the effect of CHIs between two different outcomes. Results: A total of 72 eligible randomized controlled trials involving 8592 patients and 5 CHIs were included. The results of network meta-analysis showed that RDN, XYP, and YHN had significantly better treatment performance compared to ribavirin. SHL and TRQ were obviously superior to ribavirin with respect to total clinical effectiveness. The results of surface under the cumulative ranking curve ordering and cluster analysis indicated RDN as the best intervention with respect to total clinical effectiveness, antipyretic time, and herpes disappearance time. Fifty-four studies described adverse drug reactions/adverse drug events (ADRs/ADEs) and 32 studies reported ADRs/ADEs in detail. No ADRs/ADEs were reported for TRQ. Conclusions: CHIs were found superior to ribavirin in terms of treatment performance and may be beneficial for patients with herpangina. RDN had the potential to be the best CHI with respect to all outcome measures. More evidence is required to assess the safety aspects of CHIs.